2013
DOI: 10.1007/s10620-013-2595-z
|View full text |Cite
|
Sign up to set email alerts
|

Management for CBD Stone-Related Mild to Moderate Acute Cholangitis: Urgent Versus Elective ERCP

Abstract: This study demonstrates that urgent ERCP would be recommended in the management of patients with CBD stone-related mild to moderate acute cholangitis because of the advantage of short hospital stay and intervention to discharge time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…The cure rate of cholangitis in the present study (90%) was lower than that reported in previous studies on two-stage treatment (92-94%) [5] or single-stage treatment (97.7-100%) [13]. However, the cure rate of cholangitis was 94% when alleviation of cholangitis was assessed at 7 days after treatment.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…The cure rate of cholangitis in the present study (90%) was lower than that reported in previous studies on two-stage treatment (92-94%) [5] or single-stage treatment (97.7-100%) [13]. However, the cure rate of cholangitis was 94% when alleviation of cholangitis was assessed at 7 days after treatment.…”
Section: Discussioncontrasting
confidence: 85%
“…Therefore, these findings may not always be applicable to non-severe cases of cholangitis without coagulopathy. Jang et al compared urgent and elective single-stage treatment for CBD stonerelated cholangitis and found that the cholangitis alleviation rate within 7 days of treatment was 97.7-100% and that 12.7% of all cases had complications, including mostly post-ERCP pancreatitis and bleeding in three cases (1.4%) [13]. Additionally, their study demonstrated the efficacy and safety of single-stage treatment in non-severe cases of cholangitis; however, the study was a single-center retrospective case accumulation study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate management of acute cholangitis is essential for survival [21][22][23][24]. However, acute cholangitis manifests from a broad variety of causes and with varied severity.…”
Section: Discussionmentioning
confidence: 99%